PENJABARAN STANDAR INTERNASIONAL TRIMS DAN OECD DALAM KETENTUAN HUKUM PENANAMAN MODAL INDONESIA - Supasti Dharmawan, Ni Ketut; Caka Bawa Landra, Putu Tuni; Samsithawrati, Putu Aras (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 3 (2015)DO - 10.24843/JMHU.2015.v04.i03.p11, 2015)
As a member of the WTO-TRIMs Agreement basically Indonesia has stipulated the National Treatment Principle to the legal provisions relating to investment activities. However, the Indonesian investment Law (Law No. 25 of 2007) still remains that the regulation of National Treatment with regard to national interests. In order to the difficulties may exist in domestic level such as the social, economic as well as values may be different in some member countries, the WTO-TRIMs provide exceptions for the member with notify mandatory requirement to the Board of TRIMs. Relating to investment activities other International standards also relevant to study is the GCG principles developed by the OECD. Although Indonesia is not OECD member countries, the GCG principles adopted in various Indonesian laws related to investment activities doe to it relevant and harmony to the economic, social as well as community values in order to develop capital investment.
Keywords: International Standards, TRIMS, OECD, GCG, Indonesia Investment Law